Analisis Kesulitan Belajar Matematika Dalam Menyelesaikan Soal Materi Operasi Hitung Pecahan Pada Siswa Kelas V SD Negeri Morkepek - Susanto, Dimas Kurniawan Budi; Fadlillah, M. (Yayasan Arrahman Nahdlatul Wathan, 2024)
The purpose of this study was to determine the difficulty of learning mathematics and the factors that cause mathematics learning difficulties in solving problems of fraction counting operation material in fifth grade students of SD Negeri Morkepek. This research uses a method with a descriptive qualitative approach. This research uses data collection techniques with interview techniques and documentation. The results of this study are 1). Math learning difficulties in using facts, namely students have difficulty in translating fraction story problems into a form of solution according to symbols or fraction numbers correctly. 2). Math learning difficulties in using concepts, namely students are unable to master the prerequisite concepts of fraction calculation operation material regarding determining the KPK. 3). Difficulty in using principles, namely students have difficulty in connecting the concept of fractions into the right calculation relation. 4). Difficulty in using skills, namely students are unable to complete the problem solving according to the fraction calculation procedure.